2009
DOI: 10.7547/0980023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coexisting Foot Deformity on Disability in Women with Knee Osteoarthritis

Abstract: There is a significant correlation between indicators of pain and disability (visual analog scale and WOMAC scores). Also, the presence of foot deformities increased disability levels in women with knee osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 25 publications
2
34
0
2
Order By: Relevance
“…Alterations of foot morphology in patients with knee OA are associated with knee pain, disability, and cartilage damage [1012]. Although several studies suggest the existence of a biomechanical connection between frontal knee alignment and rearfoot angle, [1622] the relationship of frontal plane alignment and foot posture of patients with knee OA has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations of foot morphology in patients with knee OA are associated with knee pain, disability, and cartilage damage [1012]. Although several studies suggest the existence of a biomechanical connection between frontal knee alignment and rearfoot angle, [1622] the relationship of frontal plane alignment and foot posture of patients with knee OA has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Flatfoot is associated with the presence of knee pain and medial cartilage damage in patients with knee OA [10]. Hallux valgus is associated with both knee and foot pain as well as the presence of nodal OA [11] and an increase in disability levels in women with knee OA [12]. A recent study showed that approximately 13–39% of individuals with knee OA, or at-risk of knee OA, have concurrent foot pain that adversely affects their functional status [13], knee symptoms [14], and clinical outcomes 1 year following total knee arthroplasty (TKA) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Methods of foot-type classification or as- 34 Two studies did not have an NF comparative group and were therefore excluded from the meta-analysis. 88, 101 The authors of 1 study did not report standard deviations or standard errors, 10 and the authors of 5 other studies did not report data on the number of lower extremity injuries (outcome) 1,12,56,72 or the number of participants (sample) 3 with each foot type.…”
Section: Foot-classification Methodsmentioning
confidence: 99%
“…Studies included in qualitative synthesis, n = 34 79 South Africa, 10 Turkey, 34 Taiwan, 41 Korea, 52 and China. 97 There were 12 prospective cohort studies, …”
Section: Study Populationsmentioning
confidence: 99%
See 1 more Smart Citation